Lessons from the financial crisis : causes, consequences, and our economic future - Kolb, Robert W., 1949- (Robert W. Kolb series in finance., 2010)
In this title, the world's best financial minds help us understand today's financial crisis. With so much information saturating the market for the everyday investor, trying to understand why the economic crisis happened and what needs to be done to fix it can be daunting. There is a real need, and demand, from both investors and the financial community to obtain answers as to what really happened and why. "Lessons from the Financial Crisis" brings together the leading minds in the worlds of finance and academia to dissect the crisis. Divided into three comprehensive sections - The Subprime Crisis; The Global Financial Crisis; and, Law, Regulation, the Financial Crisis, and The Future - this book puts the events that have transpired in perspective, and offers valuable insights into what we must do to avoid future missteps. Each section of this book is comprised of chapters written by experienced contributors, each with his or her own point of view, research, and conclusions. It examines the market collapse in detail and explores safeguards to stop future crises. It encompasses the most up-to-date analysis from today's leading financial minds. We currently face a serious economic crisis, but in understanding it, we can overcome the challenges it presents. This well-rounded resource offers the best chance to get through the current situation and learn from our mistakes